Co-creating physical activity interventions: Findings from a multiple case study using mixed methods - Popp, Johanna; Grüne, Eva; Carl, Johannes; Semrau, Jana; Pfeifer, Klaus (Frontiers in Public Health, 2022)
Introduction: In health and physical activity promotion, there is growing interest in co-creation approaches that involve researchers and non-academic stakeholders in developing new interventions. Previous research has shown the promising results of cooperative planning as a co-creation approach in building new capacities and implementing physical activity-promoting interventions in nursing care and automotive mechatronics. However, it remains unclear whether (1) cooperative planning for physical activity promotion can be successfully transferred to other settings in the nursing care and automotive mechatronic sectors and (2) what key factors influence its success or failure. Methods: We conducted a multiple case study in three settings in the nursing care and automotive mechatronics sectors. Following a mixed methods approach, we collected, analyzed, and triangulated data from documents (n = 17), questionnaires (n = 66), and interviews (n = 6). Quantitative data were analyzed descriptively and through using nonparametric analyses of variance; qualitative data were analyzed using qualitative content analysis by extraction. Results: The transfer of cooperative planning to new settings was realized, though the impact varied by setting. While the interventions were developed and implemented in nursing care settings, interventions were developed but not implemented in the automotive mechatronics setting. In this context, intervention implementation was influenced by 11 key factors: champion, commitment, embedment, empowerment, engagement, health-promoting leadership, ownership, relevance, resources, responsibility, and strategic planning. Furthermore, the transfer of cooperative planning was influenced by different activity characteristics, namely elaboration & reconsideration, group composition, number of meetings, participation, period, prioritization, and researchers’ input & support. Discussion: The present article contributes to a better understanding of a co-creation approach utilized for physical activity promotion and provides new insights into (1) the transferability of cooperative planning and (2) the associated key factors influencing intervention implementation. The success of cooperative planning varied by setting and was influenced by several activity characteristics and key factors, some of which showed complex relationships. This raises the question of whether some settings might benefit more from a co-creation approach than others. Therefore, future co-creation initiatives should carefully consider the specific characteristics of a setting to select and apply the most appropriate approach.